Academic Integrity Model Development to Improve Psychological Well-Being - Laurensius Laka; Paskalis Edwin I Nyoman Paska (International Journal Labs, 2023)
Education stakeholders in this nation have paid some attention to the issue of academic dishonesty, but it is insufficient. The nation's residents' psyche is affected by the unfavorable influence sooner or later. This study aims to develop a model that explains how academic integrity is influenced by teacher support, religiosity, and peer support, to improve students' psychological well-being. The data was obtained through a survey of 110 SMAK Bhakti Luhur Malang students and was analyzed using variance-based structural equation modeling, or partial least squares model (PLS-SEM). The preliminary result shows that teacher support, religiosity, and peer support, simultaneously or partially gave a significant effect on the academic integrity (Pr > F = 0.000 <? (? = 0.05). The second evaluation of the structural model shows that teacher support, religiosity, peer support, and academic integrity simultaneously gave a significant effect on the psychological well-being. However, peer support gave no significant effect on the psychological well-being. The conclusion entails that teacher support, religiosity, and peer support play prominent roles in the formation of students' academic integrity which in turn will affect students' psychological well-being.